Corporate Social Responsibility and Urban Regeneration - Iosif, Luminita; Donose, Simona (Acta Universitatis Danubius. Communicatio, 2022)
The idea of Corporate Social Responsibility (CSR) has gained a international influence and attention in recent years in business and cities development. In this context we can talk about urban social responsibility (USR). USR considers the necessity to monitor urban development in the diverse sectors, from public policies to architecture, from urban design to local administrations, from environmental to social issues. This article aims to designate on the importance of partnership and how CSR is a multi-dimensional tool for cities to use for their development.